Cyprus : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Cyprus. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that despite its resilience so far, the economy of Cyprus is slowing down and risks are increasing. The expected slowdown will increase credit risk in banks, which, in some plausible but unlikely extreme scenarios, could have systemic implications given the size and concentration of the banking sector. Executive Directors have endorsed the government's objective to achieve a balanced budget over the medium term. Directors have also recommended the adoption of a medium-term budget framework and more effective management of public sector liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet